Capital Inflows and the Real Exchange Rate : Analytical Framework and Econometric Evidence - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1996)
This paper examines the links between capital inflows and the real exchange rate under pegged exchange rates. The analytical framework is described, and a near-VAR model linking capital inflows, interest rate differentials, government spending, money base velocity, and the temporary component of the real exchange rate (TCRER) is estimated for Korea, Mexico, the Philippines, and Thailand. TCRER movements are associated only weakly with shocks to capital flows. Negative shocks to U.S. interest rates lead to capital inflows in Asia and a TCRER appreciation in the Philippines and Thailand. Positive shocks to government spending have a small but statistically significant effect on the TCRER for Korea.